Studi Analisis Kelayakan Ekonomi Mesin Perajang Gedebog Pisang Dengan Variasi Jumlah Pekerja - Asmara, Sandi; Novita, Dwi Dian; Suharyatun, Siti; Abdilah, Rois (Jurnal Agricultural Biosystem Engineering, 2024)
Banana stem waste can be used as raw material for animal feed by reducing the size so that it is easy to consume. The Banana Stem Chopper Machine type TEP-2 can be used to chop banana stems into pieces measuring 2-5 cm. In this research, machine testing was carried out with treatment of 1, 2 and 3 workers, then chopping analysis, break even point analysis and feasibility analysis were carried out. This research aims to determine the economic feasibility of the Banana Stem Chopper Machine type TEP-2 with how many workers will gain maximum profit. The analysis results show that chopping with 1, 2 and 3 workers is suitable for economic purposes. The best performance occurred in chopping with 3 workers which resulted in a work capacity of 1382.74 kg/hour, basic chopping costs of IDR 260.84/kg and a break-even point of 10,002.60 kg/year. Productive working hours are 6 hours per day and the price for chopped banana stems is IDR 500/kg, the potential profit is IDR 309,531,548.00/year. Keywords : Banana stem waste, chopping machine, economic analysis, feasibility analysis